(untitled) (Annals of Medical Research, 2021)
Aim: To investigate the relationship between base deficit (BD) and C-reactive protein (CRP) findings evaluated during diagnosis of infants followed up for a diagnosis of perinatal asphyxia (PA).Material and Methods: This prospective observational study included 66 cases as 33 cases treated and followed up for a diagnosis of PA in the Neonatal Intensive Care Unit of Harran University Medical Faculty Hospital, and a control group of 33 healthy infants. Using a syringe washed with heparin, a fetal blood sample of 2ml was taken from the umbilical artery of the neonates thought to have PA, and blood gases were examined in an anaerobic environment. CRP values were obtained from spectrophotometric biochemical analysis of the 2ml blood sample using an Architect C16000 device (Abbott Diagnostics, Abbott Park, IL, USA). Results: Evaluation was made of 33 infants with a diagnosis of PA hospitalised in NICU and a control group of 33 healthy infants. All the cases were statistically similar in respect of gestational week at birth (GW), birthweight (BW), and gender. In the blood gas examinations of the cord blood, pH value was determined as mean 6.9 (range, 6.50-7.06), mean BD as 17mmol/L (range, 12-28 mmol/L), and CRP values as 0.2-57 mg/dl. The CRP values of the PA cases on days 2 and 3 were determined to be significantly higher than those of the control group (p0.001). As the BD value at the time of diagnosis increased, so there was determined to be a significant increase in CRP value, and this was confirmed by the Spearman correlation test (r1:0.423, p1:0.014) (r2:0.342, p2:0.05) (r3:0.451, p3:0.009). No statistically significant relationship was determined between the pH value in blood gas and the CRP level (p:0.18). Conclusion: The results of this study demonstrated that the CRP level was statistically significantly higher in cases that developed asphyxia than in the control group. A positive correlation was determined between BD at diagnosis and CRP level. A high CRP level during treatment and follow-up can be considered for use as a supportive finding showing the severity of hypoxia.